2017
DOI: 10.3390/toxins9010031
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Toxin/Antitoxin mazEF on Growth and Survival of Listeria monocytogenes under Stress

Abstract: A major factor in the resilience of Listeria monocytogenes is the alternative sigma factor B (σB). Type II Toxin/Antitoxin (TA) systems are also known to have a role in the bacterial stress response upon activation via the ClpP or Lon proteases. Directly upstream of the σB operon in L. monocytogenes is the TA system mazEF, which can cleave mRNA at UACMU sites. In this study, we showed that the mazEF TA locus does not affect the level of persister formation during treatment with antibiotics in lethal doses, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…The presence in most isolates of the mazEF toxin-antitoxin system, which indicates efficient heat-shock-adaptation capacity [15], underlines the need to reinforce contamination prevention to reduce the risk that these bacteria pose to consumers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence in most isolates of the mazEF toxin-antitoxin system, which indicates efficient heat-shock-adaptation capacity [15], underlines the need to reinforce contamination prevention to reduce the risk that these bacteria pose to consumers.…”
Section: Discussionmentioning
confidence: 99%
“…nih.gov) and Clustal Omega (https://www.ebi.ac.uk/Tools/msa/clustalo/) for their ability to target mazF homologs in Listeria species other than L. monocytogenes. The amplification conditions were those reported by Curtis et al [15].…”
Section: Pcr Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico predictions using TADB2 reveal only two TASs in L. monocytogenes EGD-e: lmo0113-0114 and lmo0887-0888 [19]. There are a few studies investigating TAS systems in L. monocytogenes [20][21][22] focusing only on a few L. monocytogenes strains and a few TAS pairs. The following TAS pairs were identified mainly using in silico methods in the strain ATCC19117 (with their corresponding gene names in L. monocytogenes EGD-e): lmo0113-0114, lmo0887-0888, and lmo1301-1302, predicting their 3D structure and potential inhibitory peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Another report investigated the TAS lmo0887-888 of L. monocytogenes EGD-e in more detail, ruling out the classical MazF action, but without demonstrating the exact role of this TAS in L. monocytogenes [20]. They showed that lmo0887-888 does not affect the level of persister formation upon antibiotic treatment, but the expression of σ B -dependent genes opuCA and lmo0880 under sub-inhibitory norfloxacin treatment [20].…”
Section: Introductionmentioning
confidence: 99%